Characterizing fruit ripening in plantain and Cavendish bananas: A proteomics approach - Bhuiyan, F.; Campos, N.A.; Swennen, Rony L.; Carpentier, Sebastien C. (Elsevier, 2020)
The fruit physiology of banana cultivars other than Cavendish is poorly understood. To study the ripening process, samples were taken daily from plantain and Cavendish bananas and the ripening stages were determined. We present data from the green to the fully mature stage. By analyzing the protein abundances during ripening we provide some new insights into the ripening process and how plantains fruits are different. Multivariate analysis of the proteins was performed correlated to the starch dynamics. A drop in sucrose synthase and a rise of acid invertase during ripening indicated a change in the balance of the sucrose fate. During ripening, sugars may no longer be available for respiration since they are stored in the vacuoles, making citrate the preferred respiratory substrate. We found significant cultivar specific differences in granule-bound starch synthase, alpha- and beta amylases and cell wall invertase when comparing the protein content at the same ripening stage. This corroborates the difference in starch content/structure between both banana types. Differences in small heat shock proteins and in the cell wall-modifying enzyme xyloglucan endotransglucosylase/hydrolase support respectively the presumed higher carotenoid content and the firmer fruit structure of plantains.